Pengembangan Jiwa Berwirausaha Bagi Ibu-Ibu Rumah Tangga Melalui Pembuatan Asinan Viral: Pengembangan Jiwa Berwirausaha Bagi Ibu-Ibu Rumah Tangga Melalui Pembuatan Asinan Viral - Dwiyanti; Hasisa Haruna; Amaliah, Rezeki; Aslindawaty, Nur; Hamran (MAMMIRI: JURNAL PENGABDIAN MASYARAKAT, 2024)
This program is implemented in the Green Marannu Land Housing Complex, Bontomarannu District, Gowa Regency. Bontomarannu District is one of the villages that produces quite abundant rambutan fruit, but there are many mangoes that are still underutilized so that an initiative emerged to run an entrepreneurial training program in utilizing rambutan fruit into pickles that are currently viral. With this activity, there are many benefits obtained by housewives in the Green Marannu Land Housing Complex who initially could not take advantage of opportunities, finally became enthusiastic about deepening their knowledge about entrepreneurship. Furthermore, our hope as speakers for housewives is to be able to implement the results obtained.